2020
DOI: 10.1111/febs.15374
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen‐sensing mechanisms in cells

Abstract: The importance of oxygen for the survival of multicellular and aerobic organisms is well established and documented. Over the years, increased knowledge of its use for bioenergetics has placed oxygen at the centre of research on mitochondria and ATP‐generating processes. Understanding the molecular mechanisms governing cellular oxygen sensing and response has allowed for the discovery of novel pathways oxygen is involved in, culminating with the award of the Nobel Prize for Medicine and Physiology in 2019 to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 161 publications
(189 reference statements)
0
60
0
Order By: Relevance
“…Multicellular organisms have evolved homeostatic mechanisms in order to maintain cellular and tissue function upon changes of oxygen tension. Exposure of human tissues or cells to reduced oxygen concentration (a condition known as hypoxia) is encountered both during physiological (e.g., high altitude, intense exercise and embryogenesis) and pathological processes (e.g., ischemia and cancer) [71][72][73]. Hypoxia promotes dramatic reprogramming of gene expression followed by a cascade of events including switching to anaerobic production of energy, modulation of lipid metabolism, increased transport and delivery of oxygen, invasion and metastasis (in the case of cancer cells), which, overall, facilitate adaptation and survival of cells in the hypoxic environment [74][75][76].…”
Section: Hypoxia and The Hypoxic Signaling Cascadementioning
confidence: 99%
“…Multicellular organisms have evolved homeostatic mechanisms in order to maintain cellular and tissue function upon changes of oxygen tension. Exposure of human tissues or cells to reduced oxygen concentration (a condition known as hypoxia) is encountered both during physiological (e.g., high altitude, intense exercise and embryogenesis) and pathological processes (e.g., ischemia and cancer) [71][72][73]. Hypoxia promotes dramatic reprogramming of gene expression followed by a cascade of events including switching to anaerobic production of energy, modulation of lipid metabolism, increased transport and delivery of oxygen, invasion and metastasis (in the case of cancer cells), which, overall, facilitate adaptation and survival of cells in the hypoxic environment [74][75][76].…”
Section: Hypoxia and The Hypoxic Signaling Cascadementioning
confidence: 99%
“…Some mRNAs contain an RNA HRE (rHRE), a sequence which can recruit an alternative initiation complex for selective cap-dependent translation [44]. This complex involves HIF-2α, one of [11][12][13]). However, this is still a vastly unexplored aspect of the hypoxia response.…”
Section: Preferential Translation Of Hypoxia Targetmentioning
confidence: 99%
“…In recent years, non-HIF targets have been identified to be hydroxylated on prolines by PHDs (reviewed in [13]), resulting in their degradation and/or changes to downstream activity including Centrosomal Protein 192 (CEP192) [90] and Forkhead Box O3 (FOXO3) [91] by PHD1, Actin Beta (ACTB) by PHD3 [92], and AKT Serine/Threonine Kinase 1 (AKT1) by PHD2 [93]. Interestingly, a new study indicated that prolyl-hydroxylation could be crucial for GMGC kinase activation [94].…”
Section: Utilising Proteomics For the Identification Of Non-histone Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic models in several model organisms have helped identify the key roles of HIFs as well as 2-OGDs in development and disease ( Table 2 ; Supplementary Table S2 ). Furthermore, genome wide mapping techniques such as chromatin immunoprecipitation followed by sequencing (ChIP-seq), RNA sequencing (RNA-seq), and Chromatin capture have more recently been used to better understand how cells responds to changes in oxygen, but also in response to 2-OGD inhibition ([ 13 , 14 ] and reviewed in [ 15 , 16 ]).…”
Section: Introductionmentioning
confidence: 99%